Endoscopic Management of Obstructive Jaundice in Pregnancy Due to Hepatic Hydatid Disease - Singh, Aniruddha Pratap; Asif, Shujaath; Lakhtakia, Sundeep; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2020)
Liver is one of the most common site of hydatid infection. Intra-biliary rupture of the hydatid cyst is a common and serious complication that can occur during course of pregnancy. Early diagnosis and treatment as mortality is high due to cholangitis. Surgical treatment is the definitive option, however but in the presence of cholangitis and pregnancy, ERCP with biliary drainage is the preferred management option.
Keywords: pregnancy; ERCP; hydatid cyst